Our landless patria : marginal citizenship and race in Caguas, Puerto Rico, 1880-1910 - Carrasquillo, Rosa E. (University of Nebraska Press, 2006)
Our Landless Patria examines issues of race and citizenship in Puerto Rico, tracing how the process of land privatization accelerated a series of struggles for natural resources between the poorest sectors of society and the landed elite. The laws of privatization favored the landed elite and barred former slaves and their descendants from obtaining a formal title to a piece of land. In response, people of color developed an alternative citizenship that validated their livelihood, putting in motion a series of civil claims that protected people's mobility rights and their access to land. However, the rural poor's claims for a more egalitarian society, or what Rosa E. Carrasquillo calls "marginal citizenship," could not successfully transform the political exclusion of the racially mixed population because of its heavy borrowing from the Spanish legal system. In particular, marginal citizenship adopted patriarchy as a model to regulate social relations at home, failing to address gender inequalities and perpetuating class differences.